Crystal growth of Ru‐doped congruent LiNbO3 and investigation of crystalline perfection and optical properties. (1st December 2015) - Riscob, B.; Bhaumik, Indranil; Ganesamoorthy, S.; Bhatt, R.; Vijayan, N.; Zimik, Khavangkhui; Karnal, A. K.; Bhagavannarayana, G.; Gupta, P. K.
Abstract : Single crystals of undoped and Ru‐doped congruent LiNbO3 (LN) were successfully grown by the Czochralski method. The axial and radial gradient of the radio frequency furnace was controlled in order to obtain crack‐free single crystals. Wafers were cut from the grown Ru‐doped single crystal at different axial positions along the growth direction and subjected to various characterization analyses. Good optical homogeneity and low residual strain in the grown crystal is confirmed by the conoscopy patterns. Further, it is confirmed that Ru doping does not influence the optical sign of the crystal. From a high‐resolution X‐ray diffractometry analysis, it is evident that the as‐grown undoped LN crystal exhibited better crystalline perfection with a single and sharp diffraction curve in comparison to the Ru‐doped crystals, which are characterized by a broader diffraction curve. Absorption coefficient and band‐gap analysis across the axial length revealed a concentration variation of Ru across the length. Refractive index measurements carried out using a prism coupler showed variation in the optical birefringence, also due to the variation of Ru concentration at different positions of the grown single crystal.